(untitled) (Economic and Political Thought, 2013)
The treatment of neoliberalism as religion leads to a situation in which there are almost no people in the world who admit that they are neoliberals. Although it is common in Poland, especially in political parties, it is also inappropriate to understand neoliberalism as liberalism. As a result, calling people ‘liberals’ sounds like calling them names. When Donald Tusk declared his retreat from the liberal doctrine and feeling attracted to social democracy, he did not want to be a ‘liberal’, and the main Polish neoliberal, Leszek Balcerowicz, did not want to admit that he was one and he decided to ‘move’ towards a target system in the libertarian ideology that takes the form of anarcho-capitalism. The author advances and justifies a thesis that the system of neoliberalism alone has its anchorage not only in libertarianism but also in the financial spheres and because of that, in spite of the fact that it caused a disastrous crisis with its first victim – the United States, the efficient systematic reforms in this state do not lead to liberalism, which – in accordance with economic sciences – would be in agreement with the principles of the mainstream.